Peranan Maqamat Tasawuf dalam Kesehatan Mental Manusia Modern - Fatiya Izzatunissa (Gunung Djati Conference Series, 2023)
This study aims to discuss the role of Sufism in modern human mental health. This study uses a qualitative approach by applying descriptive analytical methods. The data collection technique used in this research is literature study. Data analysis techniques were carried out through the stages of inventory, classification, and data analysis. This research found the role of Sufism in modern human mental health. The presence of a sufistic concept in providing solutions is the concept of takhalli, tahalli and tajalli being aspirin for the human soul. Through the station of repentance, rectifying the wrong path, the station of asceticism, changing lifestyles, and the station of ridha' self-concept to get to know the essence of a servant who must be willing and in love with the provision of the Almighty.